IMPLEMENTASI NILAI-NILAI BUDAYA LOKAL MARIMOI NGONE FUTURU (BERSATU KITA TEGUH) DALAM MEWUJUDKAN CINTA TANAH AIR MELALUI PEMBELAJARAN KURIKULUM MERDEKA DI SMA KOTA TERNATE - Hasim, Rustam; Kamisi, Mohtar (Jurnal GeoCivic, 2023)
This research discusses the implementation of local cultural values, Marimoi Ngone Future (United We Are Firm) in realizing love for the homeland through civic education learning at Ternate City High School. The background to this research explains that Ternate Island consists of various ethnic groups, has cultural diversity and unique, exotic traditions that enrich the values of Indonesian life. Ternate Island is one of the areas in North Maluku Province which is also rich in art and culture. Ternate is still very attached to the sultanate, this is because the term Ternate refers to the four centers of the sultanate in North Maluku, namely the Ternate Sultanate, Tidore Sultanate, Jailolo Sultanate and Bacan Sultanate which is known as Moloku Kie Raha which means the four mountains of Maluku with the motto Marimoi Ngone Futuru which means United We Stand.Marimoi Ngone Futuru is found in the symbol of North Maluku in the form of a pentagonal shield, which contains various objects, as well as the inscription 1999, which is the year the North Maluku province was founded. The meaning of the image is (1). The star symbolizes the Almighty Godhead. (2). Mountains are a symbol of abundant forest product wealth. The sea is a symbol of unity and oneness. (3), Rice, cloves, nutmeg and palm leaves are symbols of prosperity. (4). Salawaku and Parang as symbols of heroism. (5). The motto "Marimoi Ngone Futuru" means United we stand. The Marimoi Ngone Futuru culture is a national treasure that is important to know, understand, develop and preserve as stated in Law no. 5 of 1992 concerning Cultural Heritage Objects, because culture reflects the identity and identity of each region.Data collection in this research was carried out through several techniques, namely observation, interviews and documentation. The data analysis technique that the researcher carried out was by using three data analysis components, namely, (1). Data Reduction (data reduction). (2), Data Presentation (data display). (3), Drawing Conclusions/Verification (conclusion/drawing verification). The final flow of data analysis is drawing conclusions and verification. The conclusions put forward are final and permanent findings that can answer research problems.Keywords: Local Cultural Values, Marimoi Ngone Futuru, Citizenship Education